THE ROLE OF ORGANIZATIONAL COMMITMENT IN MEDIATING THE INFLUENCE OF PERCEIVED ORGANIZATIONAL SUPPORT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Nanda Kusuma Wardani; I Gusti Ayu Dewi Adnyani (Adisam Publisher, 2025)
The behavior demanded by organizations today includes not only in-role behavior, which involves performing tasks according to job descriptions, but also extra-role behavior. Organizational Citizenship Behavior (OCB) is essential to address the various challenges posed by organizational changes, particularly in the context of bureaucratic reform processes. Moreover, the increasing diversity of demands in the public service sector has become a growing professional responsibility for employees. This study aims to explore and explain the role of organizational commitment in mediating the influence of perceived organizational support on organizational citizenship behavior. The research was conducted at the Office of Cooperatives and SMEs in Denpasar City. A preliminary survey indicated the presence of issues related to organizational citizenship behavior at the study site. The sample for this research consisted of 53 employees, selected using a saturated sampling method. Data collection was carried out through interviews and questionnaires. The data analysis techniques employed included path analysis using SPSS, the Sobel test, and the Variance Accounted For (VAF) test. The findings of this study reveal that perceived organizational support has a positive and significant influence on organizational citizenship behavior. Additionally, perceived organizational support positively and significantly affects organizational commitment, and organizational commitment positively and significantly influences organizational citizenship behavior. Furthermore, organizational commitment effectively mediates the influence of perceived organizational support on organizational citizenship behavior.